Bovine rod rhodopsin: 2. Bleaching in vitro upon 12C ions irradiation as source of effects as light flash for patients and for humans in space. (October 2013) - Narici, Livio; Paci, Maurizio; Brunetti, Valentina; Rinaldi, Adele; Sannita, Walter G.; Carozzo, Simone; DeMartino, Angelo
Abstract Purpose: In a previous paper, we showed that chemiluminescence from radical recombination (initiated by lipid peroxidation and propagated by polyunsaturated fatty acids [PUFA]) has a bleaching effect comparable to that caused by light on the rhodopsin of retinal rod outer segment (RdOS) prepared from bovine eyes. Photons generated by radical recombination were suggested to be the origin of phosphenes perceived as light flashes by the human eye. Irradiation with 12C carbon ions was used in this study to stimulate radical production, propagation and recombination leading to photoluminescence. Materials and methods: 12C radiation bleached RdOS rhodopsin, but structural damage increasing with the radiation dose was also observed. For this reason, only the effects on rhodopsin at doses producing next to negligible biodamage and permitting regeneration have been considered as bleaching effects. Results: 12C irradiation bleached RdOS rhodopsin, but increasing structural damage with radiation dose was also observed. For the measure of bleaching and to reveal dose response effects on rhodopsin that were able to be regenerated only results from doses producing nearly negligible biodamage have been considered. Conclusions: Recombination of radicals appears responsible for the release of photons with subsequent bleaching of rhodopsin. This effect could have an important role in the generation of the anomalous visual effects (phosphenes) experienced by patients during hadrotherapy or by astronauts in space.